2009
DOI: 10.1111/j.1439-0507.2008.01563.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of Aspergillus fumigatus protein in response to treatment with a novel antifungal compound, diethyl 4‐(4‐methoxyphenyl)‐2,6‐dimethyl‐1,4‐dihydropyridin‐3,5‐dicarboxylate

Abstract: A dihydropyridine derivative, diethyl 4-(4-methoxyphenyl)-2,6-dimethyl-1,4-dihydropyridin-3,5-dicarboxylate (2e), having potent antifungal activity against pathogenic species of Aspergillus was investigated for its possible molecular mechanism of action. The SDS-PAGE coupled with nano-high-performance liquid chromatography-tandem mass spectrometry was used directly to assess both absolute abundance and differential expression of proteins in the secretory phases of Aspergillus fumigatus under the influence of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The analysis of A. fumigatus proteins expressed differentially in untreated or that treated with antifungal protein PPEBL21 was carried out to identify gene products targeted by PPEBL21 as per the method described by Chhillar et al [14]. The A. fumigatus was cultured in asparagine broth, a synthetic medium, which was prepared by dissolving asparagine (7.0 gm), ammonium chloride (7.0 gm), potassium dihydrogen phosphate (1.31 gm), ferric chloride (0.30 gm), dextrose (10.00 gm), sodium citrate (0.90 gm), and glycerol (25.0 ml) in 1000 ml of distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…The analysis of A. fumigatus proteins expressed differentially in untreated or that treated with antifungal protein PPEBL21 was carried out to identify gene products targeted by PPEBL21 as per the method described by Chhillar et al [14]. The A. fumigatus was cultured in asparagine broth, a synthetic medium, which was prepared by dissolving asparagine (7.0 gm), ammonium chloride (7.0 gm), potassium dihydrogen phosphate (1.31 gm), ferric chloride (0.30 gm), dextrose (10.00 gm), sodium citrate (0.90 gm), and glycerol (25.0 ml) in 1000 ml of distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…A. fumigatus was cultured in the absence or presence of a sublethal concentration of SCD-1 (half of MIC 90 , i.e. 7.81 μg/mL) prepared in sterilized l -asparagine broth . Both control and treated cultures were incubated at 37 °C with continuous shaking at 200 rpm using a shaker incubator (C25KC, incubator shaker, New Brunswick Scientific, Edison, NJ, USA).…”
Section: Methodsmentioning
confidence: 99%
“…7.81 μg/mL) prepared in sterilized L-asparagine broth. 23 Both control and treated cultures were incubated at 37 °C with continuous shaking at 200 rpm using a shaker incubator (C25KC, incubator shaker, New Brunswick Scientific, Edison, NJ, USA). The germinating conidia were examined microscopically after 16 h of incubation, and the growth was seized by placing the culture flasks on ice for 30 min.…”
Section: Molecular Target Identificationmentioning
confidence: 99%
“…To identify new targets and to elucidate the molecular interactions of antifungal molecules with the fungal cell, proteomic approaches are helpful tools. Dabur et al (2007) and Chhillar et al (2009) studied the molecular mechanism of the antifungal compounds 2-(3,4-dimethyl-2,5-dihydro-1H-pyrrol-2-yl)-1-methylethyl pentanoate (DHP), a pyrrole derivative from Dature leaves, and diethyl 4-(4-methoxyphenyl)-2,6-dimethyl-1,4-dihydropyridin-3,5-dicarboxylate (2e), a chemically synthesized dihydropyridine derivative, by proteomic methods. The authors found that both DHP and 2e inhibit the expression of secreted proteins and low molecular mass antigens in A. fumigatus.…”
Section: Antifungal Substancesmentioning
confidence: 97%